Elaboración y aplicación del currículo creativo de educación inicial para mejorar la motricidad fina en los niños de 4-5 años de la Unidad Educativa Riobamba del cantón Riobamba, provincia de Chimborazo del año 2016 - Samaniego Naranjo, Myrian Jeaneth (2017)
This research was performed in the "Riobamba" High school located in Riobamba canton, Chimborazo province during the 2016 academic Year, having as study population 30 girls and 20 children from 4 to 5 years of age, where It was observed, difficulties in the development of the fine motor. The research is based on the onstructivism of Vygotsky, which is defined as the transition from the Zone of real development to the Zone of potential development here is where learning is acquired. Vygotsky considers that the human being is shaped by his personal history, his social class, his social opportunities and with it is generated an integral being. As for the methodology the design of the research is non-experimental the same that determines the actual problem encountered and seek the solution of a before to establish an after, worked using the method: deductive; With a type of research: descriptive, explanatory and field; Research design: documentary and laboratory bibliography since it was developed in the classroom; To which the observation sheet was applied. In the same way, we prop ose the development and application of a "Creative Curriculum" guide with graphic plastic techniques: cutting, modeling and painting the same one that, when developed to the maximum, helps us improve fine motor skills, containing a set of creative activities to achieve learning With quality education and warmth.